ANALISIS NILAI EKONOMI OBYEK WISATA ALAM KARANG SEWU DI KAWASAN TAMAN NASIONAL BALI BARAT, KABUPATEN JEMBRANA, BALI BARAT - Semarang, Nadhira Juniati; Siahaya, Troice Elsye; Sahureka, Mersiana (MARSEGU : Jurnal Sains dan Teknologi, 2025)
The increasing public interest in nature-based tourism encourages the importance of a deeper understanding of the economic value of tourist destinations, especially those located in conservation areas. One of the main challenges in managing nature tourism is maintaining a balance between the preservation of natural resources and their economic use for the welfare of the surrounding community. This study aims 1) To know the  characteristics of visitors in visiting the Karang Sewu Natural Tourism Object,  2).  To analys the economic value of the Karang Sewu Nature Tourism Object located in the West Bali National Park area, Jembrana Regency, through the Travel Cost Method (TCM) approach.. The results  of the study show that visitor characteristics influence the intensity and motivation of visitors in visiting Karang Sewu Tourism Object, including gender, age, distance from residence, education level, employment level, income level, source of information, tourist destination, method of visiting, vehicle used, travel time, intensity of visits and travel costs.  The average travel cost per person per visit was IDR 285,525. Based on an average number of visits of 80 people per month, an estimated economic value of IDR 22,842,000 per month or around IDR 274,104,000 per year was obtained. These findings indicate that Karang Sewu is an affordable tourist destination and contributes significantly to the local economy. The results of this study are expected to be a reference in designing sustainable and inclusive conservation-based tourism management strategies, as well as encouraging local community involvement in managing tourist destinations.